Characterization and reliability of TaN thin film resistors - Lee, T.; Watson, K.; Fen Chen; Gill, J.; Harmon, D.; Sullivan, T.; Baozhen Li (2004 IEEE International Realiability Physics Symposium, 2004)
TAN resistors are commonly used in RFIC applications and are gaining acceptance in traditional CMOS designs. TAN materials, frequently used in fabrication of Cu interconnects can easily be applied to the fabrication of thin film resistors. Deposition and integration of the films may be well controlled to produce a high precision resistor, and the temperature coefficient of resistance (TCR) characteristics of the film make it ideally suited for application across a large temperature range. While the time zero characteristics of the device are well understood, of equal importance are the device reliability properties. In this paper traditional film characteristics such as resistance distributions and TCR characteristics are presented. A voltage ramp stress is employed to identify the critical current A constant voltage stress at high temperature is utilized for reliability evaluation. Based on the stress results, a reliability degradation model is derived to express the relationship between stress condition, resistance change, and lifetime. The results demonstrate that the TAN thin film resistor is reliable over traditional IC operating ranges. While TAN resistors are robust, application conditions of the resistor typically result in significant resistive joule heating. The joule heating effects on the resistor are included in the resistor degradation model. The effects of the joule heating on reliability for neighboring structures must also be considered. The effective result is that the maximum allowed use current of the resistor might be dictated by the resistive joule heating and not necessarily the resistor reliability itself. The effect of the joule heating on neighboring structures is a subject itself and will not be covered in this paper.